Can We Co-Construct a Field of Management / Administration Engaged with the Majority? - Faria, Alexandre; Moutinho Abdalla, Márcio; Malheiros Guedes, Ana Lúcia (Organizações & Sociedade, 2021)
Dynamics contrary to the life of the majority mobilized by neo-imperial neo-liberal capitalism evolving toward neo-fascist populism has become virtually invisible to the field of Management/Administration, which is driven by dynamics of appropriation-contention focused on alternatives and transmodern epistemes of the emerging South-East. We analyze this picture of radicalization of global coloniality within the context of counterrevolutionary neoliberalism facing dynamics of dewesternization and decoloniality from a South-North dialogue between Decolonial Theory/Option and Critical Realism. By proposing a critical/decolonial transmodern framework, we unveil dynamics of invisibilization/visibilization against the life of the majority, invisibilized by market sub-theorization and dominant discourse and by the liberal university and its business/management schools. In the end, we propose to recover the expanded relevance of “administration/management” engaged with the majority, through reappropriation dynamics based on de-subalternization of non-market and ‘de-celebration’ of free market.